Reconstrucción versus amputación en pacientes con lesiones graves del miembro inferior. Recomendaciones basadas en la evidencia para la Guía de Práctica Clínica de personas amputadas de miembro inferior en Colombia (2016)
ABSTRACT: The Ministry of Health and Social Protection in Colombia and the University of Antioquia in partnership with the Javeriana University, the National University of Colombia, the Colombian associations of Physical Medicine and Rehabilitation and of Physical Therapy, developed The Clinical Practice Guideline for the diagnosis and preoperative, intraoperative and postoperative treatment of the amputee, the prosthesis prescription and the comprehensive rehabilitation. In this article the evidence and recommendations found as to the decision to amputate or reconstruct in the patient with severe limb injury are summarized. The results found in 3 systematic reviews and 10 observational studies are contradictory in terms of function, job reinstatement, psychological aspects, additional surgeries, infection, and chronic pain. In the amputee there are fewer complications and less additional surgeries; disability, psychological aspects, infection, chronic pain and functional capacity are similar between reconstructed and amputated patients; however, in order to reduce costs and improve long-term function the developer group suggested carrying out reconstruction of the lower limb instead of amputation in patients over 16 years with severe limb trauma.